A Viewpoint Commentary: Buffalo as a New Model for Long COVID-19 Study and for Recovering the SARS CoV-2 Polyclonal Neutralizing Antibody, Using an Online Affinity Column Adsorption Technology, for Therapeutic Interventional Modality in Humans: A New Multi-Purpose COVID Research Proposal - Seghatchian, Jerard (Journal of Buffalo Science, 2021)
.